C9ORF72 repeat expansion is not associated with atypical parkinsonism in the Serbian population - Marjanovic, Ana; Dobricic, Valerija; Jecmenica-Lukic, Milica; Stankovic, Iva; Milicevic, Ognjen; Dragasevic-Miskovic, Natasa; Brankovic, Marija; Jankovic, Milena; Novakovic, Ivana; Svetel, Marina; Stefanova, Elka; Kostic, Vladimir (Genetika (Beograd), 2022)
These include, among others, two forms of atypical Parkinsonism, multiple system atrophy (MSA) and progressive supranuclear palsy (PSP). This study aimed to assess the potential role of C9orf72 repeat expansions among Serbian patients diagnosed with MSA and PSP. Genomic DNA of 44 MSA patients, 73 PSP patients, and 96 controls was extracted from peripheral blood, and normal C9orf72 alleles were analyzed by standard quantitative fluorescence polymerase chain reaction (QF-PCR) and fragment analysis. Subsequently, for all samples presenting a single allele, repeat-primed PCR was performed with two different sets of primers to avoid a false-negative result. Thirty repeats were used as a pathogenic cut-off and 20-29 repeats for the intermediate alleles. No pathological C9orf72 expansions were detected in the MSA and PSP patients nor the control subjects. In the MSA group, the most common was the allele with 2 repeats, and the largest repeat number was 14. Among PSP patients, the most common allele also had 2 repeats, while the largest detected repeat size within the normal range was 17. Also, we identified one PSP patient that had an intermediate size allele (25 repeats). We did not find correlation between the number of repeats and disease onset, age at the time of examination, or disease duration in MSA or PSP patients. Regarding family history, in PSP the sum of both allele repeats numbers was higher in patients with positive family history than in sporadic cases. The results presented in this study are the first systematic assessment of C9orf72 allele sizes among patients diagnosed with MSA and PSP in the Serbian population. Although the potential role of intermediate C9orf72 repeats in neurodegenerative disorders is still to be elucidated, our results support the current knowledge that C9orf72 repeat expansions are not associated with MSA and PSP.